The dark end of the street : margins in American Vanguard poetry - Damon, Maria, 1955- (American culture (Minneapolis, Minn.), 1993)
In this volume, Damon adds an important dimension to cultural theory, revealing the struggles of one group of artists as they address important questions about art, social life, and the oppression they encounter. The author foregrounds a number of modern American poets work and lives in order to argue that the American avant-garde is located in the experimental literary works of social "outsiders." Discussing avant-garde poetry as writing that pushes at the limits of experience as well as at the limits of conventional form, Damon argues that the marginalized and oppressed, ostensibly the most expendable members of American society, have produced its truly vanguard literature.